Screening Constant by Unit Nuclear Charge Photoionization of Rb\(^{2+}\) Ions (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2019)
Photoionization data of the trans-Fe element Rb\({}^{2+}\) are reported. Rydberg series 4s\({}^{2}\)4p\({}^{4}\)(\({}^{1}\)D\({}_{2}\))nd and 4s\({}^{2}\)4p\({}^{4}\)(\({}^{3}\)P\({}_{1}\))nd Rydberg series of Rb\({}^{2+}\) from the \({}^{2}\)P\({}^°\)\({}_{3}\)\({}_{/}\)\({}_{2}\) ground state and the \({}^{2}\)P\({}^°\)\({}_{1/2}\) metastable state of Rb\({}^{2+}\) converging respectively to the 4s\({}^{2}\)4p\({}^{4}\)(\({}^{1}\)D\({}_{2}\)) 4s\({}^{2}\)4p\({}^{4}\)(\({}^{3}\)P\({}_{1}\)) series limit in Rb\({}^{3}\)\({}^{+}\) are considered.\ Calculations are performed in the framework of the Screening constant by unit nuclear charge (SCUNC) method. Accurate data are tabulated up to $n=40$.\ It is shown that the SCUNC analytical formulas reproduce with an excellent precision, recent ALS measurements of Macaluso et al. [J. Phys. B: At. Mol. Opt. Phys. 49 (2016), 235002; 50 (2017), 119501)]. The energy deviations with respect to the ALS data are equal to 0.001 eV. New data are tabulated for \(n=21-40\).
Keywords: Photoionization; Rydberg series; Ground state; Metastable state; SCUNC